ANALYSIS OF REVENUE ASSIGNMENT AUDIT FINANCIAL STATEMENTS Case Study On Public Accountants Doli, Bambang, Sudarmadji & Dadang Yogyakarta Branch Office - One, Suryadi; Isafaatun, SE., MM, Eliya (Accounting, 2009)
Research Thesis with the title Analysis of Financial Statement Audit Assignment Acceptance by Public Accountants Doli, Bambang, Sudarmadji & Dada Yogyakarta Office Fiscal Year 2008 the author conducted in December to February of 2008 with the object of study Public Accountants Doli, Bambang, Sudarmadji & Dada Office of Yogyakarta and Client Public Accountants Doli, Bambang, Sudarmadji & Dadang Office of Yogyakarta. This study aims to determine whether the procedures for receiving and analyzing financial statement audits by the Office of Public Accountants Doli, Bambang, Sudarmadji & Dadang Office of Yogyakarta has been in accordance with acceptance standards audits of financial statements that have been required by the Indonesian Institute of Certified Public Accountants. Based on the analysis that has been the author do that Public Accountants Doli, Bambang, Sudarmadji & Dadang Yogyakarta Office has implemented all requirements have been required by the Indonesian Institute of Certified Public Accountants and the Accounting Standards. In determining the ability to apply professional skills closely and carefully Public Accountants Doli, Bambang, Sudarmadji & Dadang Yogyakarta Office has undertaken this stage but not documented, as well as in identifying objec at special risk and the risk of unusual Public Accountants Doli, Bambang, Sudarmadji & Dada Yogyakarta Office can not apply this stage because at the time of the audit for fiscal year 2008 clients do not have a client who has a specialist business that Public Accountants Doli, Bambang, Sudarmadji & Dadang Yogyakarta Office did hire a professional special audits required. Keywords: Assignment, Audit of Financial Statements